2012
DOI: 10.1080/17441692.2012.701318
|View full text |Cite
|
Sign up to set email alerts
|

‘Slipping through the cracks’: Policy implications of delays in HIV treatment seeking

Abstract: Public health initiatives to “test and treat” HIV infected persons require understanding HIV care seeking. A study of 101 HIV infected women receiving anti-retroviral medications in Kampala, Uganda examined barriers to HIV care. Participants entered HIV/AIDS care late, despite knowing their risk and having sought care for symptoms. Over half the participants (51%) reported delays of up to 5 years from when they suspected they were infected to seeking an HIV test. Some women reported that they did not perceive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…For these people, the promise of ‘manageable’ HIV disease is buried under the weight of these daily struggles, most of which cannot be ‘managed’ through the health care system. McGrath and colleagues (2012) reported that even when infected persons engage with medical care, they can ‘slip through the cracks’ of the medical care system, failing to receive HIV-specific care until late in the disease process. Indeed, the very factors that increase vulnerability to HIV risk, such as poverty and lack of education, make it difficult to receive the care needed to achieve the promise of a manageable disease.…”
Section: Challenging the Paradigm: Everyday Experiences Of Artmentioning
confidence: 99%
“…For these people, the promise of ‘manageable’ HIV disease is buried under the weight of these daily struggles, most of which cannot be ‘managed’ through the health care system. McGrath and colleagues (2012) reported that even when infected persons engage with medical care, they can ‘slip through the cracks’ of the medical care system, failing to receive HIV-specific care until late in the disease process. Indeed, the very factors that increase vulnerability to HIV risk, such as poverty and lack of education, make it difficult to receive the care needed to achieve the promise of a manageable disease.…”
Section: Challenging the Paradigm: Everyday Experiences Of Artmentioning
confidence: 99%